Explaining IT programming concepts using NSM explications: The case of ‘variable’ and ‘constant’ - Bartłomiej Biegajło (LingBaW)
The paper seeks to explore a practical application of Natural Semantic Metalanguage in defining two core concepts in computer programming, i.e. the concept of a variable and the concept of a constant. The investigation of both programming concepts is carried out with reference to Apple’s Swift programming language, which is now the dominant language in creating applications designed for Apple’s devices. The explications of a variable and a constant developed in this paper are tentative definitions of the most fundamental functionalities behind the two programming concepts. They are meant to ease the learning experience of programming enthusiasts who are at the early stages of their learning path.